From Values to Practice: The Role of Religious Culture in Shaping Spiritual Intelligence Among Students at Elementary School Jember - Adyan Muhammad, Zahrul; Mas'ud, Mas'ud; Sarwan, Sarwan (Attadib: Journal of Elementary Education, 2024)
AbstractThis study aims to analyze the implementation of religious culture in fostering students' spiritual intelligence at SD Baitul Amien 1 and SD Baitul Amien 2 Jember. The research focuses on strategies for instilling religious cultural values, the development of religious culture programs, and their implications for students' spiritual intelligence. A qualitative approach was used with a case study and multi-case design. Data were collected through interviews, observations, and document analysis. The research subjects were purposively selected, including the principal, vice principal of curriculum, Islamic education teachers, and students. Data analysis followed the Miles, Huberman, and Saldana model, with data validity tested through technique and source triangulation.  The findings reveal that: (1) Strategies for instilling religious cultural values are carried out through the development of an integrated curriculum, the creation of a supportive learning environment, and the involvement of all school components; (2) Religious culture programs include congregational Duha prayer, Monday-Thursday fasting, congregational prayer, prayer habituation, honesty canteens, and the 3S culture (Smile, Greet, Salute); (3) The implementation of religious culture has multidimensional implications, encompassing spiritual-personal, social-interpersonal, and academic-intellectual dimensions. This study concludes that a structured and integrated religious culture can be an effective strategy for fostering students' spiritual intelligence in public schools.Keywords:Role, Religious Culture, Spiritual IntelligenceAbstrakPenelitian ini bertujuan untuk menganalisis implementasi budaya religius dalam menumbuhkan kecerdasan spiritual peserta didik di SD Baitul Amien 1 dan SD Baitul Amien 2 Jember. Fokus penelitian meliputi strategi penanaman nilai budaya religius, program pengembangan budaya religius, dan implikasinya terhadap kecerdasan spiritual peserta didik. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus dan rancangan multi kasus. Pengumpulan data dilakukan melalui wawancara, observasi, dan kajian dokumen. Subjek penelitian ditentukan secara purposive meliputi kepala sekolah, waka kurikulum, guru PAI, dan peserta didik. Analisis data menggunakan model Miles, Huberman, dan Saldana dengan keabsahan data diuji melalui triangulasi teknik dan sumber. Hasil penelitian menunjukkan bahwa: (1) Strategi penanaman nilai budaya religius dilakukan melalui pengembangan kurikulum terintegrasi, pembentukan lingkungan pembelajaran yang mendukung, dan pelibatan seluruh komponen sekolah; (2) Program budaya religius yang diterapkan meliputi salat Duha berjamaah, puasa Senin-Kamis, salat berjamaah, pembiasaan doa, kantin kejujuran, dan budaya 3S; (3) Implementasi budaya religius memberikan implikasi multidimensional meliputi dimensi spiritual-personal, sosial-interpersonal, dan akademik-intelektual. Penelitian ini menyimpulkan bahwa pengembangan budaya religius yang terstruktur dan terintegrasi dapat menjadi strategi efektif dalam menumbuhkan kecerdasan spiritual peserta didik di sekolah umum.Kata kunci: Budaya Religius, Kecerdasan Spiritual, Peran